Developing a Culturally Responsive Picture Storybook to Enhance Reading Literacy in Indonesian Primary Schools - Yuninda, Dewi; Rusminto, Nurlaksana Eko; Pramudiyanti, Pramudiyanti; Adha, Mohammad Mona (Lectura : Jurnal Pendidikan, 2024)
In the current era of globalization and the development of information technology, literacy skills have become critical skills that every student must master to face the challenges of the times. Literacy skills are related to reading, writing, and thinking activities that focus on increasing the ability to critically, creatively, and innovatively understand information. By reading, students will apply speaking and writing skills. Based on the results of interviews at one school, teachers have not made maximum use of interesting learning media. Therefore, it is necessary to create exciting learning media for reading skills. One of them is picture storybook media. Picture storybook media are suitable learning media to develop because engaging learning media can be used as teaching aids to illustrate material explained in related subject books. This research aims to produce picture storybooks based on the CRT approach to improve students’ reading literacy in lower grades. This research method uses the ADDIE model. Data collection uses scales, interviews, observations, and questionnaires. Data analysis techniques use descriptive analysis t-tests. In validating media, material, language, learning, and evaluation, the v-aiken results were 0.88, 0.85, 0.88, 88.3, ​​and 65, respectively, with decent classification. Then the t-test obtained a significance result 0.000, which means 0.000 < 0.05. In short, developing picture storybooks based on the CRT approach has increased students’ reading literacy in lower grades.